2015
DOI: 10.14221/ajte.2015v40n4.6
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to Professional Growth: Investigating Upper Primary School Teachers’ Perspectives on Learning to Teach Algebra

Abstract: This paper discusses upper primary school teachers' perspectives on changes to their knowledge and practice through participation in a designbased research project. It analyses their experiences using Clarke and Hollingsworth's (2002)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…Incorporating their ideas and including them as co-inquirers, motivated them as Diamond and Powell (2011) found in their study. These findings aligned with other studies, too, that a community of practice (Lave & Wenger, 1991) that included a multifaceted professional learning experience (Burke, 2013;Bertrand & Marsh, 2015;Daniels, Pirayoff, & Bessant, 2013;Kronholz, 2013;Wilkie & Clarke, 2015) provided a safe space for learning, as teachers opened up and trusted each other and were vulnerable as they shared their ideas and practices (Anderson, Feldman, & Minstrell, 2014;Bertrand & Huguet, 2015) especially in learning how to teach language (Garcia, Arias, Harris, & Serna, 2010). Similar to these studies, participants in this study, validated each other, even challenged each other, but often with laughter and support.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Incorporating their ideas and including them as co-inquirers, motivated them as Diamond and Powell (2011) found in their study. These findings aligned with other studies, too, that a community of practice (Lave & Wenger, 1991) that included a multifaceted professional learning experience (Burke, 2013;Bertrand & Marsh, 2015;Daniels, Pirayoff, & Bessant, 2013;Kronholz, 2013;Wilkie & Clarke, 2015) provided a safe space for learning, as teachers opened up and trusted each other and were vulnerable as they shared their ideas and practices (Anderson, Feldman, & Minstrell, 2014;Bertrand & Huguet, 2015) especially in learning how to teach language (Garcia, Arias, Harris, & Serna, 2010). Similar to these studies, participants in this study, validated each other, even challenged each other, but often with laughter and support.…”
Section: Discussionsupporting
confidence: 87%
“…Diamond and Powell (2011) conducted a series of studies that showed that including teachers in the iterative process in the development of learning intervention strategies proved beneficial on many levels. This multifaceted-PLC adhered to individual needs and demonstrated a pathway to professional learning (Wilkie & Clarke, 2015). Furthermore, Lane et al (2015) found that embedding coaching between professional development days aided in teacher learning as indicated by self-reports.…”
Section: Multifaceted Professional Developmentmentioning
confidence: 85%
“…Evidence of improvements in the learning outcomes of their pupils seemed to change participants' attitudes and beliefs (cf. Guskey, 2002;Wilkie & Clarke, 2015). In addition, the study's results acknowledge that work-related teacher education may be a catalyst for building human, social and identity capacity (Schuller, 2010).…”
Section: Discussionmentioning
confidence: 86%
“…Of note is the fact that only two of the seventeen studies address both types of participants, both early childhood education and primary teachers, pre-service. Wilkie and Clarke [61], Australia Analyze the perspectives of late primary school teachers involving their knowledge and practice of algebra.…”
Section: Categorization Of the Papers That Analyze Mathematical Knowledge For Teaching Early Algebramentioning
confidence: 99%
“…McAuliffe and Lubben [58] focus on the explanations provided by teachers regarding the selection of examples, representations, and modifications of an algebraic task. Wilkie [59,63] and Wilkie and Clarke [61] consider the possible correct answers that teachers provide to questions that arise over the course of a certain algebraic task, and they identify recursive and explicit generalization strategies.…”
Section: Categorization Of the Papers That Analyze Mathematical Knowledge For Teaching Early Algebramentioning
confidence: 99%